Clinical characteristics of a case series of children with coronavirus disease 2019. Issue 6 (8th April 2020) - Zhu, Li; Wang, Jian; Huang, Rui; Liu, Longgen; Zhao, Haiyan; Wu, Chao; Zhu, Chuanwu
Abstract: We reported the clinical characteristics of a case series of 10 patients with coronavirus disease 2019 (COVID‐19) aged from 1 year to 18 years. Seven patients had contact with confirmed COVID‐19 family members before onset. Fever (4 [40.0%]) and cough (3 [30.0%]) were the most common symptoms. No patient showed leucopenia and lymphopenia on admission. Pneumonia was observed in chest CT images in 5 (50.0%) patients. Five (50.0%) patients received antiviral treatment. No patient had severe complications or developed a severe illness in our study. Our study indicated that COVID‐19 children present less severe symptoms and have better outcomes.